SAT-096 Response to RHGH Therapy in Children with Isolated Short Stature with or Without an Identified Genetic Cause - De Andrade, Nathalia Liberatoscioli Menezes (J Endocr Soc, 2020)
Introduction: Children with isolated (former known as idiopathic) short stature (ISS) have been treated with rhGH with a variable response. Objectives: To evaluate the short-term response to rhGH therapy in children with ISS with or without a genetic diagnosis. Methods: We analyzed retrospectively the growth rate and height SDS change in the first year of rhGH treatment according to the presence or absence of defects in genes that regulate growth plate. The decision to start rhGH treatment was based on clinical features and the genetic results were obtained during the follow-up. Patients were enrolled in several previous genetic studies using gene candidate approach or multigene sequencing analysis. Results: A total of 51 prepubertal children (36 boys) with ISS were treated with rhGH. Thirteen of these children start puberty during the treatment and three of them were concomitant treated with GnRH analog. Basal characteristics of these children were 7.7 ± 3.2 years of age, height SDS -2.5 ± 0.8; sitting height/height (SH/H) SDS 1.2 ± 1.4; BMI SDS 0 ± 1.0 and mild delay of bone age (-1.6 ± 1.3 y). The mean target height SDS was -1.2 ± 0.9y, 18 (35%) of these children have at least one parent with height SDS < -2 and 3 (6%) both parents are short. Consanguinity was present in 3 (6%) cases. Among this cohort, fifteen children had pathogenic or likely pathogenic allele variants in genes that regulate growth plate: IHH (n = 4), SHOX (n = 9) and NPR2 (n = 2). Seven (47%) of these variants were inherited from a short stature parent. Children with or without an identified genetic cause have similar age and height SDS at the start of the treatment. A higher BMI and SH/H SDS were observed in children with genetic defects than in those without (BMI SDS 0.5 ± 1.1 vs. -0.15 ± 0.9, p = 0.02; SH/H SDS 2.0 ± 1.4 vs. 0.9 ± 1.3, p = 0.006). Additionally, children with genetic defects had a less marked bone age delay (-1.0 ± 1.3 vs. -1.9 ± 1.2; p = 0.02). Both groups were treated with similar rhGH dose (50 μg/kg/day). Patients with and without an identified genetic cause had similar improvement in growth velocity during the first year of therapy: 4.8 ± 1.6 to 8.9 ± 1.7 cm/y for patients with molecular diagnosis vs. 4.6 ± 1.2 to 8.5 ± 2.3 cm/y for those without. This resulted in similar height SDS change during this period for both groups (0.6 ± 0.3 vs. 0.6 ± 0.5 SDS for children with or without a genetic cause, respectively). Age at the start of treatment was the main variable that explains growth response variability during this first year (r(2) = 0.17, p = 0.009). Conclusion: The presence or absence of an identified genetic cause, involving genes that regulate growth plate, did not significantly influence the short-term growth response to rhGH therapy of children with ISS. Long-term follow-up is still needed to assess the final height of these children and possibly to assess whether there is a different growth rate related to each known affected gene.